2019
DOI: 10.1098/rstb.2019.0026
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating genetic links between grapheme–colour synaesthesia and neuropsychiatric traits

Abstract: Synaesthesia is a neurological phenomenon affecting perception, where triggering stimuli (e.g. letters and numbers) elicit unusual secondary sensory experiences (e.g. colours). Family-based studies point to a role for genetic factors in the development of this trait. However, the contributions of common genomic variation to synaesthesia have not yet been investigated. Here, we present the SynGenes cohort, the largest genotyped collection of unrelated people with grapheme–colour synaesthesia ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…There is already evidence of links between synaesthesia and anxiety (Carmichael et al, 2019) and between synaesthesia and PTSD, post-traumatic stress disorder (Hoffman et al, 2019). A possible link with schizophrenia has already been discussed (Tilot et al, 2019). Whatever the mechanisms behind these associations are, they are likely to require a reconceptualization of synaesthesia not just in terms of anomalous experiences (e.g., numbers evoking colour) but as a broader neurocognitive phenotype (Ward & Filiz, 2020).…”
Section: Summary and Future Directionsmentioning
confidence: 95%
See 1 more Smart Citation
“…There is already evidence of links between synaesthesia and anxiety (Carmichael et al, 2019) and between synaesthesia and PTSD, post-traumatic stress disorder (Hoffman et al, 2019). A possible link with schizophrenia has already been discussed (Tilot et al, 2019). Whatever the mechanisms behind these associations are, they are likely to require a reconceptualization of synaesthesia not just in terms of anomalous experiences (e.g., numbers evoking colour) but as a broader neurocognitive phenotype (Ward & Filiz, 2020).…”
Section: Summary and Future Directionsmentioning
confidence: 95%
“…schizotypy on some subscales, Banissy et al, 2012, and there is suggestive genetic evidence, Tilot et al, 2019).…”
Section: Predictive Processing Models Of Perceptionmentioning
confidence: 98%
“…In fact, Banissy and colleagues [140] found that synaesthetes score higher on positive schizotypy. In this respect, recent genetic analyses have found a very slight association between SZ polygenic scores and synaesthesia, although no significant association was found between synaesthesia and scores related to ASD [142]. Finally, synaesthesia and TS have also occasionally been found to co-occur in patients, with synaesthetic experiences interacting with, provoking, or being driven by tics and obsessionality [143].…”
Section: Cross-modality and Aggression: Overlaps And Intersections Among The Disordersmentioning
confidence: 99%
“…Synesthesia is associated with positive, but not negative, schizotypy 53–55 and genetic overlap is suggested. 56 We did not assess schizotypy, which is a potential limitation as higher schizotypy among our synesthetes cannot be ruled out. However, our experiment concerned perception, not positive symptoms; our groups clearly differed in their perceptual experience for letters and/or numbers, which was our focus.…”
Section: Discussionmentioning
confidence: 96%